Purchase intention toward sustainable fashion brand: analysis on the effect of customer awareness on sustainability on willingness to pay - Siauw Gabriella Tiffany Wijaya; Eristia Lidia Paramita (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2021)
Customer awareness of sustainable products has increased very rapidly during the last few years. This phenomenon has encouraged international fast-fashion brands to develop a new line which is a more sustainable line. This paper aims to examine the effect of customer awareness on sustainability and willingness to pay on purchase intention toward sustainable fashion brands. This study obtained 211 respondents with the sampling method of purposive sampling with the criteria as follow: (1) Men and women who are Indonesians, (2) Men and women who enjoyed clothes-shopping at international fast-fashion brands stores, also (3) Men and women who aged 15 – 36 years old. Multiple regressions were used as a method to conduct hypotheses test of this study. The findings of this study stated that sustainability movement awareness and willingness to pay contributes a positive and significant effect towards the purchase intention of Indonesian customers. Furthermore, this study has found that the Indonesian market is already very aware of the sustainability movement and the concerns toward environmental health.